2022
DOI: 10.3389/fresc.2022.876389
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to sustainable employment of people with acquired brain injury or spinal cord injury: The employer's perspective

Abstract: BackgroundOf those people with an acquired brain injury (ABI) or spinal cord injury (SCI) who initially successfully returned to paid employment, some exit the workforce before reaching official retirement age. Employers play a central role in ensuring a sustainable work situation for employees with a disability and in preventing such exits. However, the factors and mechanisms involved from the employer's perspective are still poorly understood.PurposeThe purpose was to determine factors which, from employer's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To address our research question, we carried out a secondary analysis of data from focus group discussions and semi-structured interviews (8, 9) that were conducted between May 2019 and July 2020. The original three studies investigated factors associated with sustainable work of persons with ABI and SCI (10)(11)(12). In the current secondary analysis, the gathered data was re-analyzed thematically (13,14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address our research question, we carried out a secondary analysis of data from focus group discussions and semi-structured interviews (8, 9) that were conducted between May 2019 and July 2020. The original three studies investigated factors associated with sustainable work of persons with ABI and SCI (10)(11)(12). In the current secondary analysis, the gathered data was re-analyzed thematically (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…The focus groups and the interviews followed the same procedure of discussing facilitators and barriers for sustainable work, service gaps and risk factors for labor market dropout. Detailed information on the data collection is published elsewhere (10)(11)(12).…”
Section: In-and Outpatient Rehabilitationmentioning
confidence: 99%
“…The original project aimed to identify barriers and facilitators to sustainable employment for individuals with a disability, specifically focusing on those with acquired brain injuries and spinal cord injuries (SCI) [33]. To respond to this study aim, we conducted focus group discussions and semi-structured interviews [34,35] with individuals with ABI and SCI [36], health and vocational integration professionals [37], as well as employers of persons with ABI and SCI [38]. Based on our finding that the availability and structure of vocational integration services were perceived as a major barrier to employment sustainability, especially for persons with ABI, we decided to conduct an in-depth secondary analysis of the qualitative data, focusing on perceived service gaps and their relation to the identified risk factors for sustainable employment of people with ABI.…”
Section: Data Source: the 'Sustainable Employment' Projectmentioning
confidence: 99%
“…The focus groups and the interviews followed the same procedure of discussing facilitators and barriers for sustainable work, service gaps and risk factors for labor market dropout. Detailed information on the data collection is published elsewhere [36][37][38]. The guidelines of the focus groups and the interviews are provided in the supplementary material (S1-S4).…”
Section: Data Collectionmentioning
confidence: 99%
“…The qualitative studies evaluated the perspectives of injured workers with ABI or SCI, health, work, or insurance professionals, and employers of persons with ABI or SCI (29)(30)(31). The qualitative study results showed that the most influential facilitators for sustained employment from the injured person's perspective are adaptation of the workplace and work schedule, a supportive social environment at home and at work, and ability to self-advocate, communicate and cope with a disability.…”
Section: Introductionmentioning
confidence: 99%